2009
DOI: 10.1017/s0022112009991522
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration, pressure and related quantities in the proximity of the turbulent/non-turbulent interface

Abstract: This paper presents an analysis of flow properties in the proximity of the turbulent/ non-turbulent interface (TNTI), with particular focus on the acceleration of fluid particles, pressure and related small scale quantities such as enstrophy, ω 2 = ω i ω i , and strain, s 2 = s ij s ij . The emphasis is on the qualitative differences between turbulent, intermediate and non-turbulent flow regions, emanating from the solenoidal nature of the turbulent region, the irrotational character of the non-turbulent regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 23 publications
6
16
0
Order By: Relevance
“…Velocities beyond the plume edge cannot be induced by viscous effects at the plume edge and must be induced by relatively long-range pressure gradients (consistent with findings for other entraining flows, e.g. Taveira & da Silva 2013;Holzner et al 2009;Terashima et al 2016). The vertical transport outside the plume, i.e.…”
Section: Discussionsupporting
confidence: 78%
“…Velocities beyond the plume edge cannot be induced by viscous effects at the plume edge and must be induced by relatively long-range pressure gradients (consistent with findings for other entraining flows, e.g. Taveira & da Silva 2013;Holzner et al 2009;Terashima et al 2016). The vertical transport outside the plume, i.e.…”
Section: Discussionsupporting
confidence: 78%
“…It was shown that the random error in the determination of velocity and acceleration derivatives is ∼10 %, which lies in the range of other PTV and particle image velocimetry (PIV) studies investigating small-scale aspects of turbulent flows (see e.g. Mullin & Dahm 2006;Ganapathisubramani, Lakshminarasimhan & Clemens 2007;Holzner et al 2009;Liberzon et al 2012). Random errors for the cases of Re 2000 and Re 8000 are comparable to the ones obtained for Re 5000.…”
Section: Experimental Jet Measurementsmentioning
confidence: 55%
“…Previous studies conducted by some of the authors have already employed the same numerical data set to examine small-scale features of turbulent entrainment (Holzner et al 2007(Holzner et al , 2008(Holzner et al , 2009Holzner & Lüthi 2011). In the current study we compare the simulations to the jet experiments described above in order to investigate certain aspects of the influence of mean shear on local entrainment.…”
Section: Direct Numerical Simulation Of a Flow With Zmsmentioning
confidence: 99%
See 1 more Smart Citation
“…More detailed spatial analyses of this region have recently been made experimentally (e.g. Westerweel et al 2002Westerweel et al , 2009Holzner et al 2007b) and numerically (e.g. da Silva & Pereira 2008da Silva & Taveira 2010).…”
Section: )mentioning
confidence: 99%